2008
DOI: 10.1088/1748-0221/3/10/p10001
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a silicon photomultiplier device for applications in liquid argon based neutrino physics and dark matter searches

Abstract: The performance of a silicon photomultiplier has been assessed at low temperature in order to evaluate its suitability as a scintillation readout device in liquid argon particle physics detectors. The gain, measured as 2.1×10 6 for a constant over-voltage of 4V was measured between 25°C and -196°C and found to be invariant with temperature, the corresponding single photoelectron dark count rate reducing from 1MHz to 40Hz respectively. Following multiple thermal cycles no deterioration in the device performance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 30 publications
5
60
0
2
Order By: Relevance
“…(2) SiPM-small decrease in PDE over the temperature range (Collazuol et al 2011); gain of SiPM as function of overvoltage has been shown to be independent from temperature and although dark counts are reduced at lower temperature (Lightfoot et al 2008, Ramilli 2009), this effect is less pronounced due to the baseline correction already being applied. The CRT curves, however, are shifted in voltage due to the change of breakdown voltage with temperature (Buzhan 2001).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…(2) SiPM-small decrease in PDE over the temperature range (Collazuol et al 2011); gain of SiPM as function of overvoltage has been shown to be independent from temperature and although dark counts are reduced at lower temperature (Lightfoot et al 2008, Ramilli 2009), this effect is less pronounced due to the baseline correction already being applied. The CRT curves, however, are shifted in voltage due to the change of breakdown voltage with temperature (Buzhan 2001).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Численное моделирование позво-ляет произвести оценку поверхностной плотности че-ренковских фотонов при энергиях первичных гамма-квантов около 5 GeV (см., например, [7,130]), которая показывает, что МЛФД, используемые как детекторы черенковского излучения, удовлетворяют требованиям полноценного функционирования наземных гамма-теле-скопов при таких низких энергиях первичных частиц. Основное преимущество МЛФД в сравнении с тради-ционными вакуумными ФЭУ заключается в том, что применение МЛФД позволяет проводить наблюдения в лунные ночи, что существенно увеличивает экспо-зиции исследуемых космических источников, а также в высокой квантовой эффективности -30−40% вме-сто 10−20% (см., например, [131,132]). Кроме этого, МЛФД проще в использовании, требуют значитель-но меньшего электрического напряжения и мощно-сти.…”
Section: проект гамма-обсерватории Alegrounclassified
“…Likewise the realistic spatial resolution of the order of one to a few millimetre, depending on hole diameter, is fully sufficient when taking into account diffusion of charges in liquid argon, see [17] and references therein. Here it is proposed to use a sparse array of existing light sensor technology, silicon photomultipliers [20], [21], in order to take fast snaphots of charged particle tracks arriving at an imaging plane. The price to pay for such a shortcut to a full digital camera option would be the requirement of reconstruction of light source locations instead of direct imaging.…”
Section: Sparse Array Readout and Reconstruction Algorithmmentioning
confidence: 99%